Improved mechanical and moisture resistance property of in situ polymerized transparent PMMA/Cellulose composites. Issue 9 (10th June 2014) - Sain, Sunanda; Ray, Dipa; Mukhopadhyay, Anirudhha
<x xml:space="preserve">Abstract</x> This article evaluates the role of cellulosic fillers in a synthetic polymer matrix like polymethylmethacrylate (PMMA) when incorporated by in situ suspension polymerization technique. Cellulose micro/nanofibers (CNF) were extracted from jute fibers and chemically modified with maleic anhydride (MACNF) to increase their interfacial compatibility with PMMA by participation of the MA moiety in the free radical polymerization with MMA. The effect of incorporating MACNF on the physical and mechanical properties of the PMMA matrix was investigated. Optical transparency was retained in the in situ prepared PMMA/cellulose composites (IPMC) similar to that of unreinforced PMMA. Another set of PMMA/cellulose composites was prepared by dispersing MACNF in PMMA matrix by ex situ solution dispersion method (EPMC). The modification of CNF with MA significantly improved the filler/matrix interfacial compatibility and in situ polymerization technique further enhanced the properties of the composites. The high moisture absorption tendency, which is a major drawback of the cellulose filled composites, remarkably reduced in IPMC. POLYM. COMPOS., 36:1748–1758, 2015. © 2014 Society of Plastics Engineers